Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species - Iwasa, Mtsuhiro (Zootaxa, 2020)
The Japanese species of the genus Cordilura Fallén are taxonomically revised. Three species, namely Cordilura katoi sp. nov., C. shinonagai sp. nov., and C. yezoana sp. nov. are described as new to science. The previous described Japanese species C. cuspidata Sasakawa, 1986 and C. nubecula Sasakawa, 1986 are remarked. Three species, C. albipes (Fallén, 1819), C. remmi Elberg, 1972, and C. richterae Ozerov & Krivosheina, 2015 are recorded from Japan for the first time. An identification key to the Japanese species of Cordilura is also provided.